Návrhy na snížení nezaměstnanosti v okrese Zlín - Trlida, Martin (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Tato práce se zaměřuje na návrh opatření, které povedou ke snížení nezaměstnanosti v okrese Zlín. Nejdříve je nezaměstnanost analyzována podle jednotlivých skupin obyvatelstva a zjišťují se problémy tohoto trhu práce. Na základě analýzy budou předloženy návrhy na snížení nezaměstnanosti, které budou zaměřeny především na ohrožené skupiny obyvatelstva.

This thesis is focusing on suggestions, which will lead to decrease in unemployment in the district of Zlín. Unemployment is analysed by individual groups of population first and then are found out the problems of this labour market. Based on the analysis will be presented proposals to reduction of unemployment, which will be focused mainly on endangered groups of population.
Suggestions for Reduction of Unemployment in the District of Zlín
Keywords: Nezaměstnanost; míra nezaměstnanosti; trh práce; aktivní politika zaměstnanosti; úřad práce; Unemployment; unemployment rate; labour market; active labour market policy; labour office